2017
DOI: 10.1016/j.ajhg.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Scale Investigation of Protein Allosteric Regulation Perturbed by Somatic Mutations in 7,000 Cancer Genomes

Abstract: The allosteric regulation triggering the protein's functional activity via conformational changes is an intrinsic function of protein under many physiological and pathological conditions, including cancer. Identification of the biological effects of specific somatic variants on allosteric proteins and the phenotypes that they alter during tumor initiation and progression is a central challenge for cancer genomes in the post-genomic era. Here, we mapped more than 47,000 somatic missense mutations observed in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 70 publications
2
51
0
Order By: Relevance
“…We confirmed that PDE10A protein levels in stage I-II NSCLC patients correlated with decreased survival. The results that we obtained for mRNA and protein expression of PDE10A are consistent among them and also with previous results reported in NSCLC [15]. These results render PDE10A and ATP10D as potentially useful prognostic and therapeutic targets in NSCLC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We confirmed that PDE10A protein levels in stage I-II NSCLC patients correlated with decreased survival. The results that we obtained for mRNA and protein expression of PDE10A are consistent among them and also with previous results reported in NSCLC [15]. These results render PDE10A and ATP10D as potentially useful prognostic and therapeutic targets in NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…Shen et al. have reported that PDE10A mutations are predicted to influence PDE10A allosteric regulation in lung adenocarcinoma; that high levels of PDE10A expression correlate with worsened lung adenocarcinoma prognosis; and that Pf‐2545920 also suppresses the growth of NSCLC cell lines. Finally, PDE10A somatic mutations have been described in up to 19% of prostate cancers and correlated with increased levels of phosphorylated C‐AMP responsive element binding protein (p‐CREB) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, how to assess the impact of these somatic mutations in the process of tumorigenesis and disease progression is a main challenge. Considering the existing observations that many somatic mutations promote tumorigenesis by rewiring protein signaling networks (3), one potential strategy is to incorporate somatic mutations with the protein structure information and investigate them at functional sites (e.g., phosphorylation sites) (48). Phosphorylation-dependent signaling network is fundamental in cellular physiology and its dysfunction plays a critical role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Well known alterations in phenotype brought about * Produces the permission block, and copyright information by changes in one or more proteins or their regulation involved in important biological pathways include Alzheimer's disease, Parkinson's disease, Huntington's disease, cancer, cystic brosis and type II diabetes [3,13,26]. Uncovering novel changes in protein structure, function and regulation, and understanding how these alterations lead to human disorders is a very active area of research in the biological community [3,5,12,13,21,26,33,37].…”
Section: Introductionmentioning
confidence: 99%